Incidence of travel : recent journeys in ancient South America - Moore, Jerry D. (University Press of Colorado, 2017)
"Drawing on personal experience and historical and archaeological studies from across South America, Moore introduces readers to archaeological sites and remains to describe what it's like to be in the field and facilitating critical thinking about what these places might have been like in the past."--Provided by publisher